2004
DOI: 10.1063/1.1773613
|View full text |Cite
|
Sign up to set email alerts
|

Stable field emission from tetrapod-like ZnO nanostructures

Abstract: Stable field emission is realized from well-separated tetrapod-like ZnO nanostructures with high purity. The ZnO nanostructures are painted on a highly doped silicon substrate covered by a Au layer with a thickness of 300nm. An emission current density of 18mA∕cm2 is obtained and degradation was not observed over a three day period. The fluctuations of the emission current are less than 2%. These experimental results indicate that tetrapod-like ZnO nanostructures are promising materials as cold cathodes for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(74 citation statements)
references
References 19 publications
1
71
1
1
Order By: Relevance
“…10 The variety of ZnO nanostructures has provided strong potential in the application of nanoscale devices. One-dimensional (1-D) ZnO nanostructures have been demonstrated in the nanolasings, 11 nanoresonators, 12 photonic crystals, 13 photodetectcors, 14 optical modulator waveguides, 15 light-emitting diodes, 16 field emitters, 17 gas sensors, 18 solar cells, 19 and so on. However, the characteristics of the nanodevices depend significantly on the shape and size of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…10 The variety of ZnO nanostructures has provided strong potential in the application of nanoscale devices. One-dimensional (1-D) ZnO nanostructures have been demonstrated in the nanolasings, 11 nanoresonators, 12 photonic crystals, 13 photodetectcors, 14 optical modulator waveguides, 15 light-emitting diodes, 16 field emitters, 17 gas sensors, 18 solar cells, 19 and so on. However, the characteristics of the nanodevices depend significantly on the shape and size of the nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…S3 of the Supporting Information). [36] Figure 3c and 3d shows typical current-density-electric-field characteristics. The turn-on field (E to ) and the threshold field (E thr ) are the electric fields required to produce a current density of 10 mA cm À2 and 10 mA cm À2 , respectively.…”
mentioning
confidence: 97%
“…Novel tetrapod-like structures, constructed from 1D nanorods, have been observed in almost all the binary II-VI compounds, [3][4][5][6][7][8][9][10][11][12] but have not been in their ternary alloys. It has also been demonstrated that these tetrapod nanocrystals have many potential applications in waveguides, [13] photodiodes, [14] transistors, [15] field emission devices, [16] gas sensors, [17] and biomolecule delivery. [18] T-ZnSSe nanostructures were synthesized by thermally evaporating Zn powder and some group VI source materials, including S, Se and SeS 2 , in a horizontal tube furnace (see the experimental section).…”
mentioning
confidence: 99%